Pristimantis tinguichaca Brito, Ojala-Barbour, Batallas & Almendariz, 2016 (Anura, Strabomantidae): Range extension and notes on variation in color pattern - Franco-Mena, Daniela (2019)
In this paper we extend the known distribution of the endemic and recently described Pristimantis tinguichaca Brito et al., 2016, a terrestrial robber frog characterized by its beige and brown to dark-brown dorsal coloration, flanks with longitudinal or diagonal cream-coloured bands which are separated by brown, and reddish iris. The new records, based on two specimens collected from the Cerro Candelaria and Cerro Mayordomo reserves of Fundación Ecominga in the upper Pastaza River watershed, Tungurahua province, east-central Ecuador, represent the northern limit of the species and extend this species to the Llanganates-Sangay ecological corridor.